1993
DOI: 10.1523/jneurosci.13-08-03549.1993
|View full text |Cite
|
Sign up to set email alerts
|

Development of individual geniculocortical arbors in cat striate cortex and effects of binocular impulse blockade

Abstract: This study analyzes the morphological changes in geniculocortical axons terminating in the primary visual cortex of the cat, during the period in which, in normal development, the terminals in layer IV undergo an eye-specific segregation. Geniculocortical afferent fibers were filled anterogradely by the Phaseolus lectin (PHA-L) injected into the main laminae of the LGN. After standard immunohistochemical procedures, single axons were serially reconstructed in two or three dimensions. Experiments were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
127
3

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(144 citation statements)
references
References 33 publications
14
127
3
Order By: Relevance
“…We found no evidence of exuberant growth followed by regression. Such a pattern of directed growth is consistent with that described for the development of other types of circuitry, including VPM TCAs to barrel cortex (Agmon et al, 1995; Catalano et al, 1996), geniculocortical inputs to cat visual cortex (Antonini and Stryker, 1993), and intrinsic barrel cortex projections (Rhoades et al, 1996; Miller et al, 2001; Bureau et al, 2004). Nevertheless, the complexity of single POm TCA arbors in adult rats (Deschenes et al, 1998) far exceeds the typical morphology we observed at P8.…”
Section: Discussionsupporting
confidence: 86%
“…We found no evidence of exuberant growth followed by regression. Such a pattern of directed growth is consistent with that described for the development of other types of circuitry, including VPM TCAs to barrel cortex (Agmon et al, 1995; Catalano et al, 1996), geniculocortical inputs to cat visual cortex (Antonini and Stryker, 1993), and intrinsic barrel cortex projections (Rhoades et al, 1996; Miller et al, 2001; Bureau et al, 2004). Nevertheless, the complexity of single POm TCA arbors in adult rats (Deschenes et al, 1998) far exceeds the typical morphology we observed at P8.…”
Section: Discussionsupporting
confidence: 86%
“…The formation or segregation of ocular dominance columns in the visual cortex of kittens is suggested to be dependent on processes of consolidation of core axon terminals or retraction of exuberant terminals (Callaway and Katz, 1992;Antonini and Stryker, 1993). This suggestion seems to be consistent with the recent observations that the column formation in the visual cortex is impaired by the application of BDNF (Cabelli et al, 1995;Hata et al, 1996), because BDNF is known to increase their branching of axon terminals (Cohen-Cory and Fraser, 1995).…”
Section: Relevance To Plasticity Of the Visual Systemsupporting
confidence: 69%
“…However, there is growing evidence for a theory of development based on construction, rather than elimination (Quartz 1999). In biological networks, selective growth and elimination of connections result in a net increase in connectivity (Antonini and Stryker 1993) and structural complexity (Katz and Shatz 1996). When neurons and connections were added to a network op coupled maps, in Gong and van Leeuwen 2003, a scale-free network resulted from the current rewiring scenario.…”
Section: Discussionmentioning
confidence: 99%